Deep RNA sequencing at single base-pair resolution reveals high complexity of the rice transcriptome - Zhang, Guojie; Guo, Guangwu; Hu, Xueda; Zhang, Yong; Li, Qiye; Li, Ruiqiang; Zhuang, Ruhong; Lu, Zhike; He, Zengquan; Fang, Xiaodong; Chen, Li; Tian, Wei; et al. (Genome Research, 2010)
Understanding the dynamics of eukaryotic transcriptome is essential for studying the complexity of transcriptional regulation and its impact on phenotype. However, comprehensive studies of transcriptomes at single base resolution are rare, even for modern organisms, and lacking for rice. Here, we present the first transcriptome atlas for eight organs of cultivated rice. Using high-throughput paired-end RNA-seq, we unambiguously detected transcripts expressing at an extremely low level, as well as a substantial number of novel transcripts, exons, and untranslated regions. An analysis of alternative splicing in the rice transcriptome revealed that alternative cis-splicing occurred in ∼33% of all rice genes. This is far more than previously reported. In addition, we also identified 234 putative chimeric transcripts that seem to be produced by trans-splicing, indicating that transcript fusion events are more common than expected. In-depth analysis revealed a multitude of fusion transcripts that might be by-products of alternative splicing. Validation and chimeric transcript structural analysis provided evidence that some of these transcripts are likely to be functional in the cell. Taken together, our data provide extensive evidence that transcriptional regulation in rice is vastly more complex than previously believed.
10.1101/gr.100677.109